Map of Charles Lennig & Company plant in Bridesburg, Pennsylvania - Rohm and Haas Company (1933)
Map depicting the facility and grounds of the Charles Lennig and Company chemical manufacturing plant in Bridesburg, a neighborhood located along the Delaware River in the Northeast section of Philadelphia, Pennsylvania. The map is color-coded to indicate when each building was erected between 1925 and 1936. Charles Lennig and Company operated as a subsidiary of the Rohm and Haas Company, an international chemical company headquartered in Philadelphia, from 1920 to 1947.
Keywords: Chemical industry; Charles Lennig and Company, Inc.; Maps; Pennsylvania--Philadelphia--Bridesburg; Rohm and Haas Company; Corporations